Effect of supplementation of maturation medium with cysteamine and two culture media (KSOMaa and SOF) on in vitro fertilization of bovine oocytes - Quintanilla M., Lisbeth (2015)
The effect of the cysteamine in maturation medium on the oocyte cleavage rate and the effect of culture media KSOMaa and SOF on in vitro embryo development rate at 8 days post-fertilization was evaluated. A total of 680 oocytes from cattle ovaries were randomly distributed in two treatments: T1 (n=321) maturation medium TCM-199 and T2 (n=359) maturation medium TCM-199 supplemented with 100 mM cysteamine. Oocytes were fertilized after 24 h with frozen semen from a single bull and cultured in KSOMaa for 18 h and the fertilization rate was assessed 72 h after division. In the second phase, after the first culture, both groups were cultivated using two culture media: KSOMaa and SOF until day 8 post-fertilization. The results of the first phase showed a cleavage rate of 43.6% for the control group and 46.0% for the cysteamine supplemented group, without difference between groups. In phase 2, the blastocyst rate was 18.0% for the TCM-199 + KSOMaa and 20.9% for TCM-199 with cysteamine + KSOMaa (p<0.05), and 15.8% for TCM-199 + KSOMaa and SOF and 18.6% for TCM-199 with cysteamine + KSOMaa and SOF (p<0.05). The results indicated that the addition of cysteamine to the culture media improved the in vitro embryo development rate to blastocyst in oocytes cultured in maturation medium TCM-199, and without differences due to the KSOMaa and SOF.